Comparison of Static Characteristics between Unregulated and Regulated Electrical Drives - Jelena Jukić Antolović; Vedrana Jerković Štil; Željko Hederić (International Journal of Electrical and Computer Engineering Systems, 2013)
In this paper, the difference between an unregulated and a regulated electrical drive in terms of power losses is analyzed. First, open loop scalar control, closed loop scalar control and speed estimated scalar control are explained. Then, static characteristics obtained by experimental measurements are analyzed and compared for different control principles. Finally, based on experimental results, it is proposed when and which drive is to be used.